Experimental fluence‐modulated proton computed tomography by pencil beam scanning. Issue 7 (8th June 2018) - Dedes, George; Johnson, Robert P.; Pankuch, Mark; Detrich, Nick; Pols, Willemijn M. A.; Rit, Simon; Schulte, Reinhard W.; Parodi, Katia; Landry, Guillaume
Abstract : Purpose: This experimental study is aimed at demonstrating, using a simple cylindrical water phantom, the feasibility of fluence‐modulated proton computed tomography (FMpCT) by pencil beam scanning (PBS) proton computed tomography (pCT). Methods: The phase II pCT prototype of the Loma Linda U. and U. C. Santa Cruz was operated using the PBS beam line of the Northwestern Medicine Chicago Proton Center. A 20 × 10 grid of 1.37 cm full width half maximum pencil beams (PB) equally spaced by 1 cm was used to acquire 45 projections in step and shoot mode. The PB pattern's fluence was modified to allow FMpCT scans with fluence modulation factors (FMF) of 50% and 20%. A central FMpCT region of interest (FMpCT‐ROI) was used to define a high image quality region. Reconstructed images were evaluated in terms of relative stopping power (RSP) accuracy and noise using annular ROIs. The FMpCT dose savings were estimated by Monte Carlo (MC) simulation of the pCT acquisitions using beam phase space distributions. PBS pCT results with homogeneous fluence were additionally compared to broad beam results in terms of RSP accuracy and noise. Results: PBS pCT scans with acceptable pileup were possible, and images were comparable to previously acquired broad beam pCT images in terms of both noise and accuracy. In the FMpCT‐ROI, the noise and accuracy from full fluence (FF) scans were preserved. Dose savings of up to 60% were achieved at the object's edge when using FMF of 20%. Conclusion: In this study, we have demonstrated that PBS pCT scans can achieve equivalent accuracy as those obtained from broad beams. The feasibility of FMpCT scans was demonstrated; image accuracy and noise were successfully preserved in the central FMpCT‐ROI chosen for this study, and dose reduction of up to 60% at the object's edge was realized.